MEANINGFUL LEARNING MODEL THROUGH CONTEXTUAL TEACHING AND LEARNING; THE IMPLEMENTATION IN ENGLISH SUBJECT - Husni Mubarok; Nina Sofiana; Diah Kristina; Dewi Rochsantiningsih (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Teaching English in the Indonesian National Curriculum demands a change in the learning paradigm towards student-centered, participatory, and contextual learning. However, there are still many teachers who do not know the true nature of English learning. Thus, it causes problems in English language teaching. This research aims at 1) determining the learning process using meaningful learning through contextual teaching and learning, and 2) improving student learning outcomes after being taught using the learning model. This study was conducted at eighth grade of SMP Islam Pecangaan, Jepara regency in which it consisted of 18 students and one English teacher. The design was collaborative classroom action research with two cycles, where in each cycle consisting of four steps; planning, acting, observing, and reflecting. The data were collected through observation, interview and test with qualitative and quantitative analysis. The finding indicated that the implementation of the meaningful learning model through CTL could 1) improve the students learning completeness from 44% in the first cycle to 89% in the second cycle, 2) improve the learning process carried out by teachers in the aspects of advance organizer, progressive differential, contextualization and constructivism, meaningful learning development, and evaluation, and 3) improve students learning outcomes in each cycle.